Fabrication of nanostructured ZnO/MgO bilayer with PVDF-TrFE layer for metal-ferroelectric-insulator-metal (MFIM) capacitor application / Habibah Zulkefle - Zulkefle, Habibah (Institute of Graduate Studies, UiTM, 2017)
The nano-MgO films, nano-ZnO films and nanostructured ZnO/MgO bilayer films were synthesized using sol-gel spin coating method. The uniform and smooth nano-ZnO film was utilized as the oxide dielectric template to produce nanostructured ZnO/MgO bilayer films. The nano- MgO films and nanostructured ZnO/MgO bilayer films were deposited at various deposition parameters (solution concentration, number of layer and annealing temperature). The effect of deposition parameters towards morphology and dielectric properties of nano-MgO films and nanostructured ZnO/MgO bilayer films was investigated. The variation of solution concentrations revealed that nano-MgO film and nanostructured ZnO/MgO bilayer film with 0.4M concentration produced improvement in the electrical properties as seen by the uniform particle distribution. The 0.4M nanostructured ZnO/MgO bilayer film showed an increment in dielectric constant, k (5.71) in comparison to 0.4M nano-MgO single layer film. Hence, 0.4M concentration was the optimized solution concentration utilized for both nano-MgO films and nanostructured ZnO/MgO bilayer films, for investigating the number of deposition layers of these films…